Epigenetic mechanisms linking pregnancy complications to cardiovascular disease in offspring - Kazim Raza Talpur; Iqra Bano; Muhammad Waleed Abdullah (Exploration of Cardiology, 2024)
Pregnancy complications such as pre-eclampsia, gestational diabetes, and intrauterine growth restriction (IUGR) not only present immediate risks to maternal and fetal health but also have long-term implications for the cardiovascular health of offspring. Emerging evidence suggests that these complications may induce epigenetic changes, which in turn predispose offspring to cardiovascular diseases (CVDs) later in life. Epigenetic modifications, including DNA methylation, histone modifications, and non-coding RNA regulation, play crucial roles in fetal development by influencing gene expression without altering the DNA sequence. Aberrant DNA methylation patterns have been observed in offspring exposed to adverse intrauterine environments, affecting genes that regulate blood pressure, lipid metabolism, and inflammation, key factors in CVDs development. Similarly, histone modifications linked to pregnancy complications can disrupt the expression of genes involved in vascular function, contributing to increased cardiovascular risk. Additionally, dysregulation of microRNAs in response to complications like gestational diabetes may influence pathways related to insulin signaling and atherosclerosis. This review synthesizes current knowledge on the epigenetic mechanisms by which pregnancy complications increase CVDs risk in offspring, highlighting potential avenues for early intervention and therapeutic strategies. Understanding these mechanisms could lead to the development of targeted interventions during pregnancy, potentially reducing the intergenerational transmission of cardiovascular risk and improving long-term health outcomes for both mothers and their children.